Hydrodynamic cavitation: A feasible approach to intensify the emulsion cross-linking process for chitosan nanoparticle synthesis - Kunming Zhang; Yun Xu; Lijin Lu; Changcan Shi; Yongchun Huang; Zhijuan Mao; Chao Duan; Xian'e Ren; Yan Guo; Chengdu Huang (Ultrasonics Sonochemistry, 2021)
Chitosan nanoparticles (NPs) exhibit great potential in drug-controlled release systems. A controlled hydrodynamic cavitation (HC) technique was developed to intensify the emulsion crosslinking process for the synthesis of chitosan NPs. Experiments were performed using a circular venturi and under varying operating conditions, i.e., types of oil, addition mode of glutaraldehyde (Glu) solution, inlet pressure (Pin), and rheological properties of chitosan solution. Palm oil was more appropriate for use as the oil phase for the HC-intensified process than the other oil types. The addition mode of water-in-oil (W/O) emulsion containing Glu (with Span 80) was more favorable than the other modes for obtaining a narrow distribution of chitosan NPs. The minimum size of NPs with polydispersity index of 0.342 was 286.5 nm, and the maximum production yield (Py) could reach 47.26%. A positive correlation was found between the size of NPs and the droplet size of W/O emulsion containing chitosan at increasing Pin. Particle size, size distribution, and the formation of NPs were greatly dependent on the rheological properties of the chitosan solution. Fourier transform infrared spectroscopy (FTIR) analysis indicated that the molecular structure of palm oil was unaffected by HC-induced effects. Compared with ultrasonic horn, stirring-based, and conventional drop-by-drop processes, the application of HC to intensify the emulsion crosslinking process allowed the preparation of a finer and a narrower distribution of chitosan NPs in a more energy-efficient manner. The novel route developed in this work is a viable option for chitosan NP synthesis.